2018
DOI: 10.1097/md.0000000000011211
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity of tissue IL-17 and tight junction proteins expression demonstrated in patients with autoimmune thyroid diseases

Abstract: Th17 cells together with their hallmark cytokine interleukin (IL)-17 were identified as crucial contributing factors in the pathogenesis of thyroid autoimmunity. The cytokine-regulated tight junction (Tj) disruption is thought to be essential in the initiation and/or development of several diseases. Still, the role of IL-17 maintaining Tj integrity in autoimmune thyroid diseases (AITDs) has not yet been evaluated. We aimed to investigate integrity of the thyroid follicle by studying immunoexpression of cellula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 35 publications
2
6
0
1
Order By: Relevance
“…Similarly, IL-17 levels in the peripheral blood and thyroid tissues did not differ significantly between adult patients with GD and controls (Qin Q et al, 2012). An increased expression of IL-17 within thyroid tissues from HT and GD patients was found also in our study (Zake et al, 2018). We observed stronger immunoexpression level of IL-17A in thyroid follicular cells in HT and GD patients when compared to patients with colloid goiter, thus suggesting that Th17 cells had an essential role in AITD pathogenesis (p < 0.001 and p = 0.007, respectively) (Fig.…”
Section: Th17 Cells and Thyroid Autoimmunitysupporting
confidence: 84%
“…Similarly, IL-17 levels in the peripheral blood and thyroid tissues did not differ significantly between adult patients with GD and controls (Qin Q et al, 2012). An increased expression of IL-17 within thyroid tissues from HT and GD patients was found also in our study (Zake et al, 2018). We observed stronger immunoexpression level of IL-17A in thyroid follicular cells in HT and GD patients when compared to patients with colloid goiter, thus suggesting that Th17 cells had an essential role in AITD pathogenesis (p < 0.001 and p = 0.007, respectively) (Fig.…”
Section: Th17 Cells and Thyroid Autoimmunitysupporting
confidence: 84%
“…Several studies have demonstrated a significant increase of Th17 lymphocytes and IL-17 in the peripheral blood and/or thyroid tissues of AITD patients, suggesting their contributions to thyroid autoimmunity. The overexpression of IL-17 within thyroid tissues from HT and GD patients compared to controls was also revealed in our previous study [17]. However, the role of interleukins in promoting the differentiation of Th17 cells has not been thoroughly evaluated in HT and GD pathogenesis.…”
supporting
confidence: 53%
“…In terms of thyroid cell injury, cytokines derived from the lymphocytic infiltrate play a key role, including their ability to stimulate the thyroid cells themselves to release proinflammatory mediators, thus amplifying and perpetuating the autoimmune response [ 3 ]. Previous studies have shown that blood and thyroid Th17 cells which secrete the cytokine IL-17 are increased in HT, as in many other autoimmune disorders, but a recent study has reported finding an additional source of IL-17 in the thyroid follicular cells themselves in HT [ 31 ]. Expression correlated with the appearance of CD68 + macrophages inside the follicle although there was no evidence to support a direct role of IL-17 in tight junction dysfunction.…”
Section: Pathogenetic Mechanismsmentioning
confidence: 99%